Integration Design Thinking to Develop Empathy, Collaboration, and Environmental Responsibility Character in Elementary School - Kustiarini Kustiarini; Yusroh Alquriyah; Moch Bayu Ibrahim S (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to explore the implementation of the Design Thinking approach in cultivating empathy, collaboration, and environmental responsibility among elementary school students. Conducted at SDN Purwokerto 1, Tayu District, Pati Regency, Central Java, this qualitative case study involved a fifth-grade teacher and students in IPAS (Science and Social Studies) learning. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using an interactive model. The findings reveal that the teacher successfully integrated the five stages of Design Thinking empathize, define, ideate, prototype, and test into contextual and collaborative learning activities. Students actively addressed real-life environmental issues, particularly waste management at the school, which fostered critical thinking, creativity, and emotional engagement. Evaluations were conducted formatively and reflectively, emphasizing student collaboration, creativity, emotional involvement, and the development of environmental responsibility. The implications of this study suggest that Design Thinking not only enhances conceptual understanding but also nurtures students’ empathy, teamwork, and environmental responsibility. The teacher’s role as a designer of meaningful, student-centered learning experiences that connect classroom learning to authentic contexts is crucial. Future research could explore the long-term effects of Design Thinking on character development and its broader application in diverse educational settings.